Isolasi Dan Identifikasi Fenotipik Bakteri Asam Laktat (BAL) Indigenous Asal Air Susu Ibu (ASI) - Nosa Septiana Anindita (Jurnal Teknologi Pangan, 2021)
Currently the use of probiotic food is growing rapidly, especially in Indonesia along with the development of fermentation technology. Most of the probiotic isolates come from abroad which has an impact on the high price of probiotic food products. Mother's milk is one source of lactic acid bacteria (LAB), which serves to maintain the balance of the digestive tract microflora and enhance the immune system. Lactic acid bacteria as probiotics have the chance to live in the digestive tract if they come from the human body. Based on this matter, it is necessary to conduct research as an effort to obtain indigenous BAL isolates from ASI. This study aims to obtain local BAL isolates from ASI through phenotypic identification. Phenotypic identification includes the morphology of colonies and cells, Gram, catalase test, motility and spore formation and biochemical identification including test of the ability to grow at various growth temperatures, low pH, salt content and formation of CO2 from glucose. Based on biochemical identification results, out of 38 BAL isolates that were successfully identified biochemically consisted of several genera of BAL namely Lactobacillus (9 isolates), Pediococcus (3 isolates) and Weisella (20 isolates).